Prevalence of Epstein-Barr virus DNA and Porphyromonas gingivalis in Japanese peri-implantitis patients - Ayako Kato; Kenichi Imai; Hiroki Sato; Yorimasa Ogata (BMC, 2017)
Abstract Background Peri-implantitis (PI) is an inflammatory reaction associated with functional deterioration of supporting bones around the dental implant. Recent studies suggested Epstein-Barr virus (EBV) is involved in the pathogenesis of periodontitis. We investigated the association between EBV and Porphyromonas gingivalis in Japanese PI patients. Methods Fifteen periodontally healthy individuals, 15 healthy implant patients and 15 PI patients were recruited. Forty five subgingival plaque samples were collected from the deepest probing pocket depth (PPD) site from each patient. Real-time PCR was used to detect EBV DNA and P. gingivalis. Results EBV and P. gingivalis were detected in 7 and 3 PPD sites of the healthy controls, in 9 and 4 PPD sites of the healthy implants, and in 13 and 14 PPD sites of the PI patients. P. gingivalis and coexistence of EBV and P. gingivalis were detected significantly higher in the PI patients than healthy controls and healthy implant patients. EBV was detected significantly higher in the PI patients than healthy controls. Conclusions Higher levels of EBV and P. gingivalis were detected in PPD sites of PI patients. These results suggest that coexistence of EBV and P. gingivalis may serve pathogenic factors cause for PI in Japanese dental patients.